Crohn’s Disease and intestinal tuberculosis: allusion and illusion - Ghosh, Chanchal Kumar (Bangladesh Journal of Medicine, 2023)
Differentiating Crohn’s disease (CD) and Intestinal tuberculosis (TB) is a diagnostic dilemma for most of the Clinicians in the developing world where ITB is endemic and CD incidence is increasing. These two granulomatus diseases are remarkably similar in their clinical, endoscopic, radiologic and pathologic features. The only exclusive features are caseation necrosis on biopsy, positive smear for acid-fast bacillus (AFB) and / or AFB culture, and necrotic lymph node on cross-sectional imaging in ITB. These exclusive features are limited by poor sensitivity ( pauci bacillary disease ) and nonspecific diagnostic criteria for CD.However, ITB is potentially curable whereas CD is incurable disease. But rate of misdiagnosis of CD and ITB range between 50% and 70% worldwide. An incorrect diagnosis and treatment may increase complications, morbidity and mortality. A high index of suspicion and critical analysis of clinical, endoscopic, histologic, microbiologic, radiologic and serologic features are required for differentiation between CD and ITB. However, therapeutic anti-tubercular therapy (ATT) trial is still required in a significant proportion of patients to establish the diagnosis. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 196